Engrams Formed in Virtual Reality Exhibit Reduced Familiarity Upon Retrieval: Electrophysiological Correlates of Source Memory Retrieval Indicate Modality‐Dependent Differences in Recognition Memory - Kisker, Joanna; Soethe, Marius; Sieverding, Jonas; Lange, Leon; Sagehorn, Merle; Schöne, Benjamin; Gruber, Thomas (The European journal of neuroscience, 2025)
ABSTRACT Initial findings linking Virtual Reality (VR)‐based encoding to increased recollection at retrieval remain inconclusive due to heterogeneous study designs and dependence on behavioral data. To clarify under which circumstances VR‐based encoding affects or enhances episodic memory retrieval, the fundamental question remains whether the encoding modality, i.e., VR or 2D‐desktops (PC), functions as a source for recollection, independent of further contextual factors. Specifically, the electrophysiological correlates (EEG) of item and source memory could objectively determine whether source retrieval fosters recollection and attenuates familiarity of VR‐encoded information (i.e., VR‐engrams) compared to PC‐encoded information (i.e., PC‐engrams). To this end, participants incidentally encoded everyday objects in VR and on a 2D desktop in a within‐subjects design, followed by unannounced old/new and source identification tasks. Our results indicate that encoding modality affects item memory only to a limited degree: Recognition memory performance, alongside the electrophysiological markers of item memory, i.e., the frontal and parietal old/new effects (FN400, LPC) and the theta band response, yielded comparable results for both engrams. Yet source memory differs depending on the encoding modality: The late posterior negativity indicated a shift towards recollection regarding the retrieval of VR‐engrams compared to PC‐engrams. This shift might result from attenuated familiarity with VR‐engrams, particularly reflected in the alpha band and phase‐amplitude coupling of theta and gamma band. In conclusion, encoding modality functions to some degree as a relevant source for recognition memory. Yet our results propose that familiarity is more strongly affected than recollection if contextual information beyond dimensionality is matched between encoding modalities. The study examines whether the retrieval of virtual reality (VR)‐engrams is more profoundly based on recollection than on familiarity compared to PC‐engrams, and whether the encoding modality functions as a relevant source information for episodic memory retrieval. To this end, participants incidentally encoded everyday objects in VR and on a conventional PC in a within‐subjects design. In a subsequent unannounced recognition task, participants discriminated between old objects presented during encoding and new objects, functioning as distractors (old/new task; item memory). If a stimulus was rated old, participants were asked to indicate the object's source by means of the encoding modality, i.e., VR or PC (source identification task; source memory). Our results indicate that encoding modality affects item memory only to a limited degree, whereas source memory differs depending on the encoding modality. Our results propose that familiarity is more strongly affected than recollection if contextual information beyond dimensionality is matched between encoding modalities.